The first schizomid from a dry forest in South America (Arachnida: Schizomida) - Ruiz, Gustavo R.s.; Valente, Roberta M. (Zootaxa, 2017)
Schizomids are arachnids typically found on the ground of areas with rainforest, living in the moist litter. Here we describe Surazomus algodoal sp. nov. from a coastal, dry environment on an island of the state of Pará, Brazil, in the Atlantic Ocean. Only one male has been collected, but the morphology of the flagellum is unique. Surazomus algodoal sp. nov. represents the first epigean schizomid living only in a dry forest and the easternmost record for Surazomus Reddell & Cokendolpher. The type of dry vegetation in which the animal was found covers only a small area and is endangered by human use. The new species is considered critically endangered using the IUCN criteria.